Menjadi Manusia yang Utama Menurut Alasdair Macintyre - Loho, Ambrosius Markus; Rorah, Ignatius Rolly Coun; Pontoan, Karen Alfa (Indo-MathEdu Intellectuals Journal, 2024)
Virtue is the power and ability of a person to become a whole human being. In the current context, humans need to understand about virtue as the focus of philosophers in reflecting in unity with humans. There is a misunderstanding of human beings including related to human virtues. This research will provide a correct understanding of the concept of the ultimate human, so that humans can understand correctly. The method used is descriptive analysis method and qualitative research type. Based on these steps, the author finds that the main human being or the one who has virtues, must have responsibility for self, responsibility for others and responsibility for the world. In line with that, this paper will elaborate on the importance of forming a superior moral actor subject in terms of virtue, which has unity with human life itself.